Perceived acceptance, intention to use and actual use behavior of digital information technologies among nursing professionals in Shanghai: a cross-sectional study - Hui Xie; Pengjie Zhang; Wei Zhu (BMC Nursing)
Abstract Background Digital information technologies (DITs) can contribute to optimizing the quality and efficiency of healthcare delivery. However, profiles of awareness and use behavior of DITs among Chinese nursing professionals remained limited. This study aimed to investigate the profiles of perceived acceptance, intention to use and use behavior of DITs and identify influencing factors among nursing professionals in hospitals in Shanghai. Methods A total of 1421 nursing professionals from 20 hospitals across Shanghai were selected as participants between August and October 2021. After excluding missing values, 1395 participants were included in the analyses. Using the technology acceptance model, perceived acceptance of general DITs was measured as perceived ease of use (PEU) and perceived usefulness (PU). Intention to use and use behavior were measured using two single 5-point Likert scales. Linear and logistic regression models and mediation analyses were developed to examine influencing factors. Results All of the PU and PEU items received affirmative responses (agree or strongly agree) among over 50% of participants. Of all participants, 1101 (78.9%) expressed intention to use DITs; 626 (44.9%) were frequent users. Age, bachelor’s degree, in-house training on DITs, school-based training, and out-of-hospital training were associated with perceived acceptance. Licensed practical nurse, deputy chief nurse, working years, in-house training, and school-based training were significant predictors of intention to use. Vocational college diploma, bachelor’s degree, in-house training, school-based training, out-of-hospital training, tertiary level 1 and tertiary level 2 hospitals, and specialized hospitals were associated with frequent use. Intention to use mediated 42.6% (95%CI: 10.3% ~ 60.4%) of the total effects of perceived acceptance on frequent use of DITs. Conclusions This study suggests that although nursing professionals in Shanghai have positive perceived acceptance and strong intention to use DITs, they rarely use DITs in their practice. Therefore, policies and interventions should be developed to enhance the integration of DITs into nursing professionals’ daily practice.